DOI: 10.11606/d.6.2014.tde-03112014-131343
|View full text |Cite
|
Sign up to set email alerts
|

Porções de alimentos e número de refeições realizadas por adultos e idosos do muncípio de São Paulo: relação com excesso de peso e perfil lipídico

Abstract: À Cristiane Sales, por ser uma pessoa tão prestativa e carinhosa, por compartilhar suas experiências e pelas nossas boas risadas juntas. Á Michele de Castro, pelo carinho, doçura, sabedoria e por nossas deliciosas conversas científicas e não científicas. À Bartira Gorgulho, por sua prestatividade e pelos momentos de descontração. A todos os membros do GAC, além dos já citados, Ágatha, Eliseu, Soraya e Marcela. Obrigada a todos pelas experiências vividas, aprendizados, congressos, aulas, almoços no bandejão, ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Furthermore, eating more frequently during the day reduces hunger. It increases satiety, and appetite increases the desire to consume high caloric foods, such as UPF (29,30) and fried foods, which was a mediator between the number of meals eating per day and our outcome, the UPF consumption. Besides, the habit of consuming fried foods is considered unhealthy and is associated with the belief that healthy foods are tasteless (47) .…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Furthermore, eating more frequently during the day reduces hunger. It increases satiety, and appetite increases the desire to consume high caloric foods, such as UPF (29,30) and fried foods, which was a mediator between the number of meals eating per day and our outcome, the UPF consumption. Besides, the habit of consuming fried foods is considered unhealthy and is associated with the belief that healthy foods are tasteless (47) .…”
Section: Discussionmentioning
confidence: 86%
“…The number of meals eating per day and the high fried food intake were associated with the UPF consumption. The consumption of three main meals, including breakfast, combined with smaller meals, is described as part of a healthy diet capable of regulating metabolism and body weight (29,30,47) . An accelerated pace of life can damnify meal times, including the daily consumption of breakfast, supporting an energy overcompensation along the day (28) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are some amino acids, such as glycine, which is being used in the treatment of patients suffering from enterocolitis because they have cytoprotective and anti-inflammatory action [7,8,9,10]. Glycine is a simple, non-essential amino acid known as a functional supplement used in the pharmaceutical industry, nutritional supplementation [10] and is bioactive compounds with anti-inflammatory activity present in colostrum [11,12,13]. Previous work showed that the adsorption of glycine onto Polyethylene glycol (PEG) microsphere was able to stimulate the colostrum macrophages and suggest that the controlled delivery system of glycine may be an additional mechanism of protection and treatment of patients with infections and/or inflammation gastrointestinais, as well as for the functioning of colostrum cells [7].…”
Section: Introductionmentioning
confidence: 99%